Benefits for emotional regulation of contact with nature: a systematic review - Ríos-Rodríguez, María Luisa; Rosales, Christian; Hernández, Bernardo; Lorenzo, Maryurena (Frontiers in Psychology, 2024)
Exposure to natural environments, such as parks, forests, and green areas, is often linked to a decrease in stress, anxiety and depression, while contributing to improved emotional well-being. These observations are supported by well-established theories, such as the Stress Reduction Theory and Attention Restoration Theory, which highlight the psychological benefits of interacting with nature. However, the relationship between exposure to nature and emotions, and in particular, with emotional regulation, is an evolving aspect of research with no clear conclusions. Emotional regulation can be deliberate in nature, where individuals voluntarily participate in modifying various aspects of their emotions, such as their type, intensity, quality or duration. Alternatively, it may be automatic, originating from sensory perception and acting without full awareness, but significantly influencing emotional experiences. In this context, the environmental self-regulation hypothesis, suggests that people consciously or unconsciously use their physical environment to regulate their emotions. To analyze the evidence of the relationship between contact with nature and emotional regulation, we conducted this review. Using the PRISMA statement as a reference, we conducted keyword searches in five databases in the period between 2013 and 2023. The databases selected were Scopus, Web of Science (WoS), PubMed, PsycINFO and ScienceDirect. In addition, a manual search was carried out of journals in the research field. Initially, from which grey literature, reviews and duplicates were removed in a first step. The resulting articles were then filtered using their titles and abstracts. Subsequently, the abstracts of the 25 selected articles were reviewed and discussed by researchers to reach a final decision based on consensus about the adequacy of each paper. Finally, nine articles were included in the systematic review. In general terms, this review suggests that research on the relationship between contact with nature and emotional regulation provides valuable insights into how natural environments can contribute to the emotional well-being and physical and mental health of the population.